2014
DOI: 10.1093/conphys/cou039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural environmental conditions on faecal glucocorticoid metabolite concentrations in jaguars (Panthera onca) in Belize

Abstract: We performed immunoassay and environmental validations to assess the effects of natural environmental exposure of jaguar faeces on glucocorticoid metabolites. Glucocorticoid concentrations were stable for 5 days with the corticosterone RIA. Scat aging by morphology was unreliable. Environmental validation is needed to determine field sample collection protocols for elusive species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…It is not clear why water exposure resulted in an elevation in fGCM concentrations in some studies (Washburn and Millspaugh, 2002; Mesa-Cruz et al ., 2014) but not in the present study. Some possible reasons are as follows: (i) water might cause changes in metabolite immunoactivity that can be picked up by some enzyme immunoassays or radioimmunoassays but not by others (Mesa-Cruz et al ., 2014); (ii) there could be differences in faecal forms (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear why water exposure resulted in an elevation in fGCM concentrations in some studies (Washburn and Millspaugh, 2002; Mesa-Cruz et al ., 2014) but not in the present study. Some possible reasons are as follows: (i) water might cause changes in metabolite immunoactivity that can be picked up by some enzyme immunoassays or radioimmunoassays but not by others (Mesa-Cruz et al ., 2014); (ii) there could be differences in faecal forms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Some possible reasons are as follows: (i) water might cause changes in metabolite immunoactivity that can be picked up by some enzyme immunoassays or radioimmunoassays but not by others (Mesa-Cruz et al ., 2014); (ii) there could be differences in faecal forms (e.g. elephant dung is voluminous and highly fibrous, bird faeces are in the form of powder, and deer faeces are small dense pellets) or other unmeasured variables that might be influencing the interaction between water and the metabolism of the glucocorticoids present in the faeces; (iii) the high humidity in the tropical environment might also affect samples not treated with water and thus confound the effect of the water treatment; and (iv) it is possible that the amount of water used in our experiment was insufficient to affect fGCM concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Washburn & Millspaugh (2002) found that white-tailed deer (Odocoileus virginianus) faeces that had been exposed to rainfall had artificially inflated FGM levels. By contrast, jaguar (Panthera onca) faecal samples exposed to sunlight did not show a change in FGM concentrations (Mesa-Cruz et al, 2014). However, wet conditions altered metabolite levels after five days of exposure (Mesa-Cruz et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…By contrast, jaguar (Panthera onca) faecal samples exposed to sunlight did not show a change in FGM concentrations (Mesa-Cruz et al, 2014). However, wet conditions altered metabolite levels after five days of exposure (Mesa-Cruz et al, 2014). Consequently, the authors suggested running sample transects every three to four days in both wet and dry seasons (Mesa-Cruz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%